On the density of states of graphene in the nearest-neighbor approximation - Ananyev, V.O.; Ovchynnikov, M.I. (Condensed Matter Physics, 2017)
We propose an alternative analytical expression for the density of states of a clean graphene in the nearestneighbor approximation. In contrast to the previously known expression, it can be written as a single formula valid for the whole energy range. The correspondence with the previously known expression is shown and the limiting cases are analyzed.